World development report 1992: Development and the Environment (Oxford Univ, 1993)
This book presents an alternative path-one that, if taken, would allow the coming generation to witness improved environmental conditions accompanied by rapid economic development and the virtual eradication of widespread poverty. First, it presents an accelerating programs for reducing poverty, removing distortions that encourage the wasteful use of energy and nature resources, clarifying property rights to encourage people and communities to manage resources better, and expanding programs for education (especially for girl), family planning services, sanitation and lean water, and agricultural extension, credit and research. Second, the book describes targeted measures that can bring dramatic improvements in environmental quality at modest cost in investment and economic efficiency